74.8k views
0 votes
Substituting the equation x=4y - 12 into the equation -2y= x- 6. will produce what equation?

User WhatWhat
by
5.4k points

1 Answer

6 votes

Explanation:

Given that,

x=4y - 12 ....(1)

And

-2y= x- 6 ....(2)

Put equation (1) in equation (2). So,

-2y= (4y - 12)- 6

-2y = 4y - 12 -6

-2y-4y = -12-6

-6y = -18

y = 3

So, substituting x=4y - 12 into the equation -2y= x- 6 will produce y = 3.

User Niklascp
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.